SOSIALISASI STANDAR KEAMANAN PANGAN BERBASIS HAZARD ANALYSIS AND CRITICAL CONTROL POINTS (HACCP) PADA UMKM MOMO MOCHI - Gustany, Eko Widodo; Kurniawan, IB Indra Widi; Restuasih, Sinta; Haryudiniarti, Ayu Nurul; Harjiyanto, Kun; Yulianti, Rachma (Universitas Mataram, 2025)
Mochi is a specialty food from Sukabumi, West Java, made from glutinous rice. This food has potential food safety risks that need to be considered. This socialization aims to evaluate the application of Hazard Analysis and Critical Control Points (HACCP) system in mochi production at Momo Mochi MSME. HACCP is a system used to identify, evaluate, and control food safety hazards. The purpose of this service activity is to raise awareness among Momo Mochi MSME stakeholders about the importance of food safety and the application of the HACCP system. The method used is through interviews, with the owner of Momo Mochi UMKM, observation of Momo Mochi UMKM production site, socialization of HACCP material delivery. The evaluation was carried out by asking questions before and after the delivery of the material. The results of this activity were, 71% showed a significant increase in understanding of HACCP. In addition, the implementation of personal protective equipment in the form of gloves, masks and headgear can reduce the risk of contamination, thus increasing consumer confidence.